Implementing, connecting, and evaluating a standard-based integrated operating room within a German university hospital - Dees, Raluca; Merzweiler, Angela; Schneider, Gerd; Ahlbrandt, Janko; Wagner, Martin; Kenngott, Hannes Götz; Müller, Beat P.; Bergh, Björn (ACI Open, 2018)
Background Digital operating rooms (ORs), when optimally designed and integrated, can reduce the complexity of the surgery suite. However, many integrated ORs are effectively isolated from other IT systems in the hospital because there is little or no connectivity with them. Within the German flagship project OR.NET, concepts and components were developed for a standard-based connection of the OR with hospital IT systems. Objectives The aim of this work was to implement and evaluate OR.NET concepts and components within the existing IT landscape of a German university hospital. This article describes and evaluates the implemented architecture and processes for connecting a demo OR to existing hospital IT systems at Heidelberg University Hospital. Methods For the design, establishment, and evaluation of standard-based connections of the demo OR with hospital IT systems, the iterative method “Design and Creation” with four iterations was applied. Results A generic and a concrete architecture for several standard-based connection concepts of the demo OR were developed. Furthermore, the concrete architecture was implemented and evaluated for its technical and clinical relevance. The main benefits of the project were the establishment of basic requisites for improving the efficiency within the OR, easier operation of medical devices as a result of harmonized human-machine interfaces, and providing additional data for improving healthcare. Conclusion OR.NET concepts for a standard-based connection of the OR with hospital IT systems have proven to be promising. They can serve as a reference for further integration scenarios in other hospitals.